Development of holistic vs. featural processing in face recognition - Nakabayashi, Kazuyo; Liu, Chang Hong (Frontiers in Human Neuroscience, 2014)
According to a classic view developed by Carey and Diamond (1977), young children process faces in a piecemeal fashion before adult-like holistic processing starts to emerge at the age of around 10 years. This is known as the encoding switch hypothesis. Since then, a growing body of studies have challenged the theory. This article will provide a critical appraisal of this literature, followed by an analysis of some more recent developments. We will conclude, quite contrary to the classical view, that holistic processing is not only present in early child development, but could even precede the development of part-based processing.